Acrylonitrile-butadiene-styrene-based composites derived from "fish-net"-inspired Pickering emulsion for high-performance electromagnetic interference shielding and thermal management. (February 2022) - Wang, Yating; Xin, Ziyan; Shen, Jiajun; Zhao, Lunyu; Wang, Bijia; Feng, Xueling; Mao, Zhiping; Sui, Xiaofeng
Abstract: Conductive polymer composites (CPCs) are highly desirable to address the electromagnetic radiation and heat accumulation issue associated with highly integrated electronics. Herein, we report an effective and adaptive strategy to construct a conductive pathway within the acrylonitrile-butadiene-styrene (ABS) matrix using Pickering emulsion as a designer platform. The non-covalently driven "fish-net" assembly of regenerated cellulose (RC) and graphene nanoplatelets (GNPs)/carbon nanotubes (CNTs) at the emulsion interface results in a continuous three-dimensional (3D) conductive network. As expected, the resultant composites exhibit high electrical conductivity of 261.1 S/m, excellent EMI SE of 73.5 dB and thermal conductivity of 4.17 W/mK at 27.8 wt% GNPs and 3 wt% CNTs loadings. Therefore, the Pickering emulsion interfacial assembly strategy exhibits great potential in fabricating high-performance dually-conductive EMI shielding materials. Graphical abstract: Image 1 Highlights: AG x C y composites are fabricated using Pickering emulsion as designer platform. The non-covalently driven "fish-net" assembly mechanism of RC/GNP/CNT is proposed. The prepared composites exhibit highest EMI SE of 73.5 dB.